Pengaruh Strategi Pemasaran Media Sosial dan Personal Selling Terhadap Peningkatan Penjualan Produk Nazia Hijab - Zaeni, Putri Anastasya Herdianti; Isyanto, Puji; Sumarni, Neni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study analyzes the "Impact of Social Media Marketing Strategies and Personal Selling on the Increase in Sales of Nazia Hijab Products." Using a quantitative verifiable approach, data were collected through questionnaires distributed to respondents who are customers and followers of the Nazia Hijab social media accounts. The data were analyzed using multiple linear regression. The study findings indicate that both social media marketing strategies and personal selling contribute significantly to increasing sales. These results underscore the importance of leveraging social media and personal selling as integral components of marketing strategies to boost sales in the competitive hijab industry. The findings suggest that a combination of digital marketing and direct personal approaches can serve as an effective strategy to enhance competitiveness and sales performance amidst the tight market competition for hijabs in Karawang.